Modelling of road–embedded transmitting coils for wireless power transfer. (December 2020) - Torchio, Riccardo; Cirimele, Vincenzo; Alotto, Piergiorgio; Freschi, Fabio
Highlights: Concrete affects Wireless Power Transfer coils embedded in the road pavement. The PEEC method coupled with hierarchical matrices speed-up parametric analysis. All the electromagnetic phenomena are considered by the proposed method. Graphical abstract: Abstract: The present work stems from practical experiences in the implementation of a wireless power transfer charging lane based on transmitter coils directly embedded under the road surface. After the embedment, unexpected phenomena appeared which strongly modified the behavior of the coil, thus compromising the effectiveness of the system. This paper proposes the development of a dedicated numerical method based on the Partial Element Equivalent Circuit approach and low–rank compression techniques based on Hierarchical matrices and Adaptive Cross Approximation which allows optimized parametric analysis for the investigation of the main parameters that influence the behavior of the device. The proposed numerical approach is efficiently applied to an embedded transmitting coil with parametric material parameters of the road model. However, the proposed approach is general and can be applied for the study of different electromagnetic devices.